HUBUNGAN BEBAN KERJA DENGAN KINERJA PEGAWAI DI RUANG SEKRETARIAT DINAS KESEHATAN PROVINSI ACEH - Rosita, Sri (Jurnal Kesehatan Ilmiah Aufa Royhan, 2021)
The workload experienced by employees of the Aceh Provincial Health Office Secretariat room during the Covid-19 pandemic increased, not only inside the building but also outside the building. such as the formation of a task force to deal with covid-19 so that the workload of employees outside the building and inside the building increases. The purpose of this study was to determine the relationship between workload and employee performance in the Aceh Provincial Health Office secretariat room. This research is a descriptive analytic study with a cross sectional design. This research was conducted from October 7 to November 2 2020 in the Aceh Provincial Health Office secretariat room using the interview method. The research sample was 86 respondents with total sampling technique. Univariate and bivariate data analysis. From the results of the chi-square statistical test, it can be concluded that there is a relationship between workload and employee performance with a p value of 0.01. It is hoped the leadership in the secretariat room, is to evaluate the workload assigned to employees and according to their fields of expertise so that good performance can be maintained.